PENGAJIAN KITAB BULU>G AL-MARA>M DALAM MAJLISUZZIKR BRUNEI DARUSSALAM: KAJIAN HADIS - Mukaromah, Kholila (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
ewline"> This article studies hadiths used in Majlisuzzikr led by Habib Abdul Hamid al-Mahdaly in Brunei Darussalam context. The object of this research islimited by investigating the recording video of the lectures on BulÅ«g alMarÄm, composed by Ibn ajar al-â€˜AsqalÄnÄ«, that can be downloaded fromcyberspace, you tube. However, the study of hadith there has a close relationwith the government that put into effect the Islamic law (syariat). Theexistence of hadith study in this Majlis apparently is inclined to supportthe government of Sultan Hassanal Bolkiah. According to the Alfatihmapping of explanation (pensyarh} an), this hadith study can be classifidto the category of classical explanation with bayani reasoning. For examplerelation to hadith explaination about the Prophetâ€™s daily activities to givepriority from right to left that said by Al-Mahdaly that is everyone thatcontradict with it will be accused as neglectful person and because of it canbe entered to the hell in the hereafter